Phosphorus–nitrogen compounds: Part 60: Synthesis of hexaminomonoferrocenyl-spiro(N/O)cyclotetraphosphazenes: Spectral and electrochemical properties, tuning of redox feature, and antituberculosis activity. (2nd January 2023) - Binici, Arzu; Elmas, Gamze; Okumuş, Aytuğ; Güzel, Remziye; Şimşek, Hülya; Kılıç, Zeynel
Abstract: In the present investigation, the condensation reaction of octachlorocyclotetraphosphazene, N4 P4 Cl8 (1 ) (tetramer, OCCP ), with sodium 3-(N-ferrocenylmethylamino)-1-propanoxide (L ) resulted in the formation of the starting compound hexachloromonoferrocenylspiro(N/O)cyclotetraphosphazene (2 ). Thereafter, reactions of spiro (2 ) with excesses of 1-(2-aminoethyl)pyrrolidine, 1-(2-aminoethyl)piperidine and 4-(2-aminoethyl)morpholine in dry THF gave hexaaminomono-ferrocenylspiro(N/O)cyclotetraphosphazenes, 2a, 2b, and 2c, respectively. These new products were prepared for investigation of spectral and electrochemical properties, tuning of redox features, and examination of antituberculosis activities. The structures of 2a–2c were elucidated using elemental analysis, mass spectrometry (ESI-MS), FTIR, HMBC, HSQC, 1 H, 13 C { 1 H}, and 31 P { 1 H} NMR data. The electrochemical behavior of these products containing monoferrocenyl group was investigated. Their use as potential alternative electrolyte redox couples for dye-sensitized solar cells (DSSC) was examined. The findings may inspire solar cell studies to explore the redox mediator behind the working mechanisms of DSSCs. Conversely, the antituberculosis activities of three compounds were examined against Mycobacterium tuberculosis H37Rv. The MIC values of 2a and 2 b were found to be as 30 and 35 µg/mL, respectively, against the H37Rv reference strain. Graphical Abstract: UF0001